Folktales of ‘The Wager on the Wife’s Chastity’ Type and the Old Russian Versions of Bieniasz Budny’s “A Tale of a Merchant” (episodes from the first part) - Rzepnikowska, Iwona (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
Russian folktales which belong to ‘The wager on the wife’s chastity’ type (882 in The Aarne–Thompson tale type index) owe their origin to the tale of Zinevra from The Decameron (II, 9) by Giovanni Boccaccio. Adapted by the Old Russian literature, it gradually became part of the oral tradition and underwent the process of folklorization. It should be stressed, however, that the tale was not translated directly from Italian but from Polish, and that it was Historia o kupcu [A tale of a merchant] by Bieniasz Budny that played the role of the mediating text. The reception of the Old Russian translation of the tale was quite favourable, as evidenced by the existence of five versions and the fact that their authors did not limit themselves to passively reproducing the original. Analysis of episodes from the first part of the tales of the faithful wife shows that folk creators were mainly inspired by two Old Russian versions of Tale of a merchant: A facetious tale and A strange tale. In addition, traces of inspiration drawn from the byliny about Stavr Godinovich can be found there as well as from tales of other unfairly slandered beauties, for instance those about a merchant’s daughter.